Weekly cycles of global fires—Associations with religion, wealth and culture, and insights into anthropogenic influences on global climate. Issue 21 (14th November 2015) - Earl, Nick; Simmonds, Ian; Tapper, Nigel
Abstract: One approach to quantifying anthropogenic influences on the environment and the consequences of those is to examine weekly cycles (WCs). No long‐term natural process occurs on a WC so any such signal can be considered anthropogenic. There is much ongoing scientific debate as to whether regional‐scale WCs exist above the statistical noise level, with most significant studies claiming that anthropogenic aerosols and their interaction with solar radiation and clouds (direct/indirect effect) is the controlling factor. A major source of anthropogenic aerosol, underrepresented in the literature, is active fire (AF) from anthropogenic burning for land clearance/management. WCs in AF have not been analyzed heretofore, and these can provide a mechanism for observed regional‐scale WCs in several meteorological variables. We show that WCs in AFs are highly pronounced for many parts of the world, strongly influenced by the working week and particularly the day(s) of rest, associated with religious practices. Key Points: Weekly cycles in meteorological parameters are largely caused by anthropogenic aerosols Weekly cycles in active fires are highly pronounced for many parts of the world Cycles strongly influenced by the working week and the day(s) of rest linked to religion